Optimization Injection Molding Parameters of Polypropylene Materials to Minimize Flash Defects Using the Taguchi Method - Fahmi, Nur Kholish Ali; Bintara, Redyarsa Dharma; Suprayitno (Proceeding International Conference on Religion, Science and Education, 2022)
The demands and consumption of plastic in Indonesia, especially in the food and beverage industry, iarehigh. 892 industries produce a rigid packagi, flexible packaging thermoforming, and extrusion with an average production capacity is more than 23.5 ton per year with 70% utility. The utilization of plastic in many fields is owing to the fact that the characteristics of plastic could replace other materials function. The production process of injection molding machine in bioball spike product in the industry is not completely perfect. There is a flash product defect that leads to loss in the process and production costs. The Taguchi method is selected to get the optimal parameter in minimizing the flash defect. The flash defect of product could be a big problem for a manufacture company specialized for injection molding. The product defect should be avoided or fixed by counting, analyzing, optimizing the parameters which affect its defect. This study was conducted using experimental method by determining the experiment design through fractional factorial L9 (34) for three cycles of injection trial where the test specimen was using bioball spike product with polypropylene material. The parameters used in this study were injection speed, injection pressure, injection time, and melt temperature which all of them was consisted in third level. The study used analysis of means (ANOM) and verified using Taguchi method for getting the average effect in every parameter of its level and getting the plot effect. Analysis of variance (ANOVA) was also used for knowing the average effect of its parameter towards the output, it is aimed to verify the Taguchi method. The result showed that this parameter combination is optimal in minimizing the flash defect and effect of its parameter. The results obtained determine the effect of each parameter, namely the injection speed parameter (IS) has the most significant effect of 37.91%, the injection pressure parameter (IP) has an influence of 32.17%, for the injection time (IT) parameter has an influence of 1.2%, and for the melt temperature (MT) parameter it is 28.72%. The optimal combination of parameters to cause flash defects with a combination of parameters (IS) at level 2 (40 cm/s), (IP) at level 2 (40 kg/cm2), (IT) at level 3 (5 seconds), and (MT) at level 1 (180 ?). The results of the comparison of S/N Ratio Smaller the Better before optimization (initial design) and after optimization (robust design) get a gain of 5.609.